Analisis Kesalahan Siswa SMP dalam Menyelesaikan Soal Setara AKM Numerasi Ditinjau dari Gaya Belajar - Devinta Safa Salsabila; Ismail; Nonik Indrawatiningsih (MATHEdunesa, 2026)
This study is a qualitative descriptive study that analyzes students' errors with the aim of describing the errors made by junior high school students in terms of visual, auditory, and kinesthetic learning styles using Newman's error indicators. The research data consists of the learning styles of the subjects and the results of the Minimum Numeracy Competency Assessment test. It was obtained from the learning style questionnaire and the students' answers to the questions using Newman's indicators as well as interviews between the researcher and the research subjects. The subjects taken for this study were 3 students out of 32 students of Junior High School. Each of them has different learning style visual, Auditory, kinesthetic. Moreover, the chosen subjects are those who had the highest learning style questionnaire scores for each type of learning style. Additionally, based on the results of students' answers to the Minimum Numeracy Competency Assessment questions, the researcher conducted interviews with the three selected subjects and analyzed their answers further to identify errors. The results of the study indicate that interm of there is cognitive levels of reasoning concepts. Student with a visual learning style made errors in understanding the questions, performing transformations, processing the final answers, and drawing conclusions from the final answers. student with auditory learning styles made mistakes in transformations, processing final answers, and drawing conclusions from final answers. Meanwhile, student with kinesthetic learning styles made mistakes in transformations, processing final answers, and drawing conclusions from final answers.